Influence of Input Value and Labor Expenditure on Output Value: A Case of Micro and Small Scale Industry in Indonesia - Tongam Sihol Nababan; Elvis Fresly Purba; Jongkers Tampubolon; Jongkers Tampubolon (Integrated Journal of Business and Economics (IJBE), 2020)
Objectives of the study are: (1) to estimate the influence of input value and labor expenditure on the output of micro and small industries in Indonesia, (2) to analyze the form of translog production function that is compatible with micro and small industries in Indonesia. The analytical method used is descriptive method and analysis of translog production functions with scenarios: linear translog function, complete second-order or quadratic linear translog function, and linear translog function with interaction. Results showed that (1) the function of linear translog production with interaction was more suitable used to estimate the production output of micro and small industries in Indonesia, (2) input value and labor expenditure had a positive and significant effect on output values, (3) micro-industry enterprises more emphasis on the allocation of larger workforce, while small-scale industry emphasizes greater allocation of input value, (4) the allocation of input value and labor expenditure are more efficient in micro-industries compared to small-scale industries.